Progression: an analysis of 30 years (1431- 1460) Hijri moon crescent's data in Malaysia / Mohd Zawawi Mohamad. - Mohamad, Mohd Zawawi (2011)
This study is about the analyzing the 30 years (1431 Hijri-1460 Hijri) moon crescent data in Malaysia. The data of the moon crescent are prepared by using the Moon Calculator software version 6.0. The moon crescent data are important in order to determine the visibility of moon crescent and it was used as a reference by the astronomers. There are three (3) visibility conditions of moon crescent which are the latitude, elongation and age. The moon crescent data were analyzed according to these three (3) criteria where each condition has a minimum value that must be met by the moon crescent. The moon crescent data were analyzed in form of graph profile. Since the period of this study is 30 years, each condition are divide into 5 years so that the comparisons can be seen clearly.